Culprit vessel revascularization first with primary use of a dedicated transradial guiding catheter to reduce door to balloon time in primary percutaneous coronary intervention - Guo, Jincheng; Wang, Guozhong; Li, Zixuan; Liu, Zijing; Wang, Yujie; Wang, Senhu; Wang, Yuntao; Wu, Yongxia; Wang, Haotian; Wang, Yuping; Zhang, Libin; Hua, Qi (Frontiers in Cardiovascular Medicine, 2022)
Background The effect of a single transradial guiding catheter (STGC) for culprit vessel percutaneous coronary intervention (PCI) first on door-to-balloon (D2B) time remains unclear. Methods Between February 2017 and July 2019, 560 patients with ST-elevation myocardial infarction (STEMI) were randomized to either an STGC group (n=280) or a control group (n=280) according to direct culprit vessel PCI with an STGC. The primary endpoint was D2B time, and the secondary endpoint included catheterization laboratory door-to-balloon (C2B), procedural, fluoroscopy times, and major adverse cardiac events (MACE) at 30 days. Results The median D2B time was significantly shorter in the STGC group compared to the control group (53.9 vs. 58.4 min; p=0.003). The C2B, procedural, and fluoroscopy times were also shorter in the STGC group (C2B: 17.3 vs. 24.5 min, p<0.001; procedural: 45.2 vs. 49.0 min, p=0.012; fluoroscopy: 9.7 vs. 11.3 min, p=0.025). More patients achieved the goal of D2B time within 90 min (93.9% vs. 87.1%, p=0.006) and 60 min (61.4% vs. 51.1%, p=0.013) in the STGC group. Radial artery perforation was significantly reduced in STGC group compared with control group (0.7% vs. 3.2%, P=0.033). MACE at 30 days was similar (2.5% vs. 4.6%, P=0.172) between two groups. Conclusions Electrocardiogram-guided immediate intervention on culprit vessel with an STGC can reduce D2B, C2B, procedural, and fluoroscopy times. (ECG-guided Immediate Primary PCI for Culprit Vessel to Reduce Door to Device Time; NCT03272451).